2005
DOI: 10.1093/ageing/afi101
|View full text |Cite
|
Sign up to set email alerts
|

Does ingestion of cranberry juice reduce symptomatic urinary tract infections in older people in hospital? A double-blind, placebo-controlled trial

Abstract: despite having the largest sample size of any clinical trial yet to have examined the effect of cranberry juice ingestion, the actual infection rate observed was lower than anticipated, making the study underpowered. This study has confirmed the acceptability of cranberry juice to older people. Larger trials are now required to determine whether it is effective in reducing UTIs in older hospital patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 11 publications
2
74
0
1
Order By: Relevance
“…Two studies reported that cranberry juice may be protective in subgroups of older adults, 21,22 but the effectiveness of cranberry capsules in the protection against UTI in vulnerable older persons in LTCFs has not been studied.…”
mentioning
confidence: 99%
“…Two studies reported that cranberry juice may be protective in subgroups of older adults, 21,22 but the effectiveness of cranberry capsules in the protection against UTI in vulnerable older persons in LTCFs has not been studied.…”
mentioning
confidence: 99%
“…Several trials have indeed missed the calculated UTI recurrence rates necessary to show differences between groups. 49,51,52 In one trial not a single event occurred. 52 This problem should be overcome by recruiting patients with a true high recurrence risk indicated by a pattern of .5 UTI/year rather than on the basis of a recent UTI, as most trials up to now have done.…”
Section: The Mixed Evidence From Clinical Trialsmentioning
confidence: 99%
“…51,53,55,56 To give an example, only 21/376 (5.6%) of hospitalized patients (mean age 81.5 years) had a clinical UTI within a follow-up of 35 days and an intervention period of 18 days in the study by McMurdo et al 51 At that low event rate, the study time had been too short to find differences, which may well have become evident at a longer study duration. The risk of underdosing has led investigators to apply different doses of cranberry products 38,[57][58][59] or to simply administer the highest available cranberry dose.…”
mentioning
confidence: 99%
“…However, there is no sufficient clinical evidence that cranberry type-A proanthocyanidins are effective at lowering the risk of urinary tract infection (Guay 2009, Jepson et al 2012, Vasileiou et al 2013. Some authors did not show the effectiveness of cranberry used versus placebo (McMurdo et al 2005). Dugoua et al (2008) suggest that consumption of cranberry in pregnancy is safe but they also indicated that there is no direct evidence of safety or harm to the mother or fetus as a result of consuming cranberry during pregnancy.…”
Section: Introductionmentioning
confidence: 99%